DXA-Derived Adiposity and Lean Indices for Management of Cardiometabolic and Musculoskeletal Frailty: Data Interpretation Tricks and Reporting Tips - Minetto, Marco A.; Busso, Chiara; Lalli, Piera; Gamerro, Giulia; Massazza, Giuseppe (Frontiers in Rehabilitation Sciences, 2021)
Proper assessment and follow-up of obesity and sarcopenia is relevant for the proper management of the complications of cardiometabolic and musculoskeletal frailty. A total body Dual-energy X-ray Absorptiometry (DXA) scan should be systematically incorporated in the rehabilitative routine management of patients with obesity and sarcopenia. In the former patients, total body DXA can be used to assess the fat tissue amount and distribution, while in the latter patients it can be used to quantify the reduction of appendicular lean mass and to investigate the inter-limb lean mass asymmetry. This tutorial article provides an overview of different DXA-derived fat and lean indices and describes a step-to-step procedure on how to produce a complete DXA report. We suggest that the systematic incorporation of these indices into routine examinations of obese and sarcopenic patients can be useful for identifying patients at risk for cardiometabolic and neuromuscular impairment-related comorbidities and for evaluating the effectiveness of pharmacological and rehabilitative interventions.